The Adoption of Circular Business Models in Germany: an Analysis of the DAX40 Companies - Mounir Al-Naami; Kay H. Hofmann; Kai-Michael Griese (Circular Economy and Sustainability, 2023)
In view of the rapid depletion of natural resources and the associated overloading of the biological ecosystem, the concept of circular business models (CBMs) is increasingly discussed in the literature as well as in business practice. CBMs have the potential to significantly reduce the demand for natural resources. Despite their increasing relevance, the diffusion of CBMs in business practice is largely unexplored. Consequently, this article investigates the extent to which CBMs have already been adopted by large German companies. To answer this question, the annual and sustainability reports of the members of the DAX40 are analyzed for the presence of five specific types of CBMs. Data was gathered for the years 2015 and 2020 in order to describe the development over time. The results show an increasing prevalence of CBMs in the DAX companies. In addition, it is noticeable that CBM types that serve to close material cycles are implemented more frequently than those that decelerate material cycles. In particular Sharing Platforms and Product as a Service stand out due to comparatively low adoption. Potential reasons for these findings are discussed and managerial as well as policy implications suggested.
Keywords: 330; Circular economy; Business models; Circular business models; DAX40